Implementasi User Acceptance Testing (UAT) Pada Pengujian Sistem Informasi Akademik dan Keuangan Santri - Devinka Putri; Riki Afriansyah; Putri Armilia Prayesy (TeIKa, 2025)
The digitization of administration in Islamic boarding schools is an important requirement for improving the effectiveness of academic and financial data management for students. The manual system that was previously used sometimes caused delays in reporting, risks of recording errors, and limited access to information for parents and administrators. Based on these needs, the researcher developed and evaluated a website-based Academic and Financial Information System for students at an Islamic boarding school to support transparency in reporting and ease of access. The system was developed using a prototyping approach utilizing the Laravel framework. The system was tested using the User Acceptance Testing (UAT) method, which involved 31 respondents as direct users. The UAT instrument consisted of 22 questions covering user-friendliness, user satisfaction, system functionality, and system performance. The test results showed that all aspects received a “very good” rating with the following average percentages: ease of use 88.5%, satisfaction 91.05%, functionality 90.07%, and performance 89.6%. These findings confirm that the system has worked according to the operational needs of the Islamic boarding school, is capable of managing academic, financial, and student savings data in an integrated manner, and supports the involvement of guardians through real-time access to information. Then, the system is considered feasible to implement and has the potential to improve the quality of administrative services in Islamic boarding schools.